Information Seeking Behaviour of Shrimp Farmers and their Perception towards Technology Dissemination through Mobile Phones - PR, Anand; M, Kumaran (Journal of Extension Education, 2017)
A study was conducted among the shrimp farmers to ascertain their information seeking behaviour and perception concerning extension service through mobile phones. The findings indicate that the farmer respondents were of the perception that mobile phone-aided extension service is a viable, expedient, prompt, cost-effective and novel approach. Further they expressed that a dedicated mobile app on shrimp farming with dynamic content modules on ‘disease diagnosis, calculations for water quality corrections, feed management, pond risk management and post your query ’would be very useful for farmers and extension workers to update their capacity and sharing of field experiences. Therefore, developing a mobile app on shrimp farming, incorporating the above features would enhance the access to quality information and minimise the information gap among the shrimp farmers.